FAST Heroes: Results of Cross-Country Implementation of a Global School-Based Stroke Education Campaign - Tsakpounidou, Kalliopi; van der Merwe, Jan; Klinke, Marianne Elisabeth; Webb, Chris; Ouriques Martins, Sheila Cristina; Proios, Hariklia (Frontiers in Public Health, 2022)
Background: Educating the at-risk population about stroke symptoms and requirement of calling an ambulance when stroke strikes is challenging. This exploratory cross-country study provides insights to the FAST Heroes educational campaign and outcomes hitherto achieved. Aims: The primary aim of the study was to measure the transfer of stroke-related knowledge to parents after a global school-based FAST Heroes educational campaign for 5–9-year-old children in 14 different countries. The secondary aim was to evaluate parents and teachers’ acceptability towards the program. Methods: The duration of the program was 5 hours and 1 hour per week, joining weekly face-to-face educational sessions with workbooks, cartoons, web-based learning, and other fun activities. Outcomes were measured before implementation (t1), after implementation (t2), and at six-month follow-up (t3). Program acceptability and stroke knowledge were evaluated by feedback surveys for teachers and parents. Results: Worldwide, 4,202 parents completed the program with their children and answered surveys at t1 and t2. They increased their knowledge of three stroke symptoms from 48% to 83% (p<0.001). All three surveys were completed by 86 parents, who improved their knowledge of stroke symptoms, 55% (t1), 79% (t2), and 94% (t3) (p<0.001). Overall, the educational messages were successfully passed onward. Conclusions: Findings confirm the primary aim of the study that is knowledge about stroke transfer well from children to their families through the FAST Heroes program. Second, parents and teachers globally consider the program feasible and worthwhile. The results will inform further rollout of the campaign.